MARIGOLD FLOWER (CALENDULA OFFICINALIS L.) EXTRACT LIPOSOME FORMULATION AND EVALUATION OF ITS IN VITRO ANTIOXIDANT AND ANTI-PROTEIN DENATURATION ACTIVITIES - Brigita, Beatrice
Antioxidant is a substance that can inhibit free radicals. One of the plants that has a potential to be used as the source of natural antioxidants is marigold flower. In this research, the optimal formulation of marigold flower extract liposome is determined and its antioxidant and anti-protein denaturation activities are evaluated. The evaluation of liposome’s stability when stored for 30 days in various temperatures 4, 25, and 40ºC is also done. The method used for testing liposome’s antioxidant activity is by using DPPH, while its anti-protein denaturation activity is measured by the method of protein denaturation inhibition using bovine serum albumin (BSA) as the protein model. The IC50 value of extract, liposome containing extract, and the positive control will be compared to determine whether or not there is an increase in the antioxidant and anti-protein denaturation activities in the liposome. The formulation of liposome contains lipids phosphatidylcholine and cholesterol, and extract. The optimal formulation of liposome is achieved using a total of lipid concentration of 6 mM and a total of marigold flower extract of 5% (w/v) per 10 mL dosage form. The characteristics of the liposome are measured, the particle size of the liposome is 240,4 ± 0,26 nm, its polidispersity index at 0,27 ± 0,01, its zeta potensial at - 45,24 ± 3,54 mV, pH at 4,51 ± 0,03, and its entrapment efficiency is 92,4 ± 0,02%. In the antioxidant activity testing, the IC50 value of marigold flower extract is 128,1 ± 0,2 µg/mL, liposome is 58,8 ± 2 µg/mL, meanwhile the value for ascorbic acid is 1,71 µg/mL. Next, the IC50 value measured in the anti-protein denaturation test is 195,95 ± 5,12 µg/mL for the extract, 97,69 ± 0,75 µg/mL for the liposome, and 179,91 ± 3,1 µg/mL for natrium diclofenac. The stability evaluation shows marigold flower extract liposome is stable to be stored at temperatures 25ºC and 40ºC. Liposome containing 0,5% (w/v) marigold flower extract in 10 mL dosage form increases the antioxidant and anti-protein denaturation activities of marigold flower extract.